Relationship of personal self-esteem and self-concept motives - Jelić, Margareta (2009)
The aim of this research was to investigate the relationship between the level and stability of personal self-esteem and self-relevant feedback recall i.e. which of the opposed motives, self-enhancement or self-verification, will prevail in individuals with certain type of self-esteem. Participants were 598 high-school and university students, who filled in Rosenberg's self-esteem scale (repeatedly), Self-liking self-competence scale and Implicit Association Test measuring implicit self-esteem. Results confirm the self-reference effect and generally support the mnemic neglect model.